DIGITAL IMAGE PROCESSING FUNDAMENTALS USING THE OCTAVE-ONLINE WEB USER INTERFACE - HUAMANÍ NAVARRETE, Pedro (2021)
This article describes the fundamentals of digital image digital processing using a free-access, web user interface called Octave-Online. This interface is part of the GNU operating system software applications, as well as it is known as the equivalent of Matlab in free versión; for this reason, this tool was chosen in order to give a practical approach to the use of ten basic techniques of spatial processing of digital images. To do this, we started by collecting 8 files with image contents in JPG and with different characteristics such as high and low contrast, high and low frequency, shades of gray, and intensity of colors, to put the proposed processing techniques into practice. Subsequently, some guidelines were provided for access, upload of JPG files, creation of * .m extension files, and knowledge of certain tools offered by the Octave-Online web user interface. Then, the programming code was implemented using a group of commands, for the group of the 10 techniques developed in said interface; thus we have, binarization, negative, conversion of color and gray formats, geometric transformations, histogram manipulation and spatial filtering.